Sizing a PV-Wind based hybrid system using deterministic approach. (1st August 2018) - Anoune, Kamal; Laknizi, Azzeddine; Bouya, Mohsine; Astito, Abdelali; Ben Abdellah, Abdellatif
Highlights: Meteorological data analysis for the site under study is presented. Dynamic simulation using a designed TRNSYS model of PWHS is illustrated. Integration cost of an optimized hybrid configuration for both methods is studied. Economic and environmental results such as payback period and CO2 mitigation. YAM and WM serve to size a grid-tied and off-grid PWHS respectively. Abstract: A designed model based on TRNSYS software is used to size a hybrid electrical renewable energy system that can be used to supply electrical load demands. The goal is to maintain a constant storage temperature of bitumen by compensating the thermal losses of bitumen tank through an immersed electrical heater. The developed model simulates the annual performance of different configurations of PV-Wind based Hybrid System (PWHS). It also provides the optimum configuration, which in turn, ensures supplying the needed energy with the lowest investment cost. On the other hand, a comparison study of two size deterministic methods, the yearly average month (YAM) and the worst month (WM) methods, is presented. The analysis of the designed TRNSYS model pinpoints the hybrid system requirements and the integration cost, and so far, assesses the economic and environmental impacts. Finally, the yearly average month method has served to size a grid-tied hybrid system with a lower integration cost compared to the worst month method. It's important to note that the latter method also has served to size adequately in the isolated area.